Notice x = -3 + 3y (based on your second equation), so substitute this for x into your first equation to solve for y:
-2x + 7y = 10
-2(-3 + 3y) + 7y = 10
6 - 6y + 7y = 10
6 + y = 10
y = 4
Now plug this into the other equation to solve for x:
x = -3 + 3y
x = -3 + 3(4)
x = -3 + 12
x = 9
ANSWER: x=9, y=4
NRT
2006-11-12 12:54:18
·
answer #1
·
answered by New Rule Tomorrow 2
·
4⤊
0⤋
From the given linear system with two unkowns, i.e.
[eqn1] -2x + 7y = 10
[eqn2] x - 3y = -3,
we notice that from [eqn2], we can express x as follows:
[eqn3] x = 3y - 3.
By plugging [eqn3] to [eqn1] we get
-2(3y - 3) + 7y = 10.
From this equation, we can solve for y as follows
-6y + 6 + 7y = 10
-6y + 7y = 10 - 6
[eqn4] y = 4.
Using the information for y in [eqn4], we plug this to [eqn3] to obtain the value for x. That is,
x = 3(4) - 3
x = 12 - 3
x = 9.
Therefore, pair x = 9 and y = 4 satisfies that given linear system of two unknowns defined in [eqn1] and [eqn2].
2006-11-12 13:02:06
·
answer #2
·
answered by rei24 2
·
1⤊
0⤋
-2x+7y=10
x-3y=-3
equate x
x-3y=-3
x=3y-3
subst. for x in:
-2x+7y=10
-2(3y-3) + 7y=10
-6y + 6 + 7y =10
6 + y =10
y =10-6
y=4
solve for x
x - (3(4))= -3
x -12 = -3
x =9
Check
-2x+7y=10
-2(9) + 7 (4) = 10
-18 + 28 = 10
10 = 10
2006-11-12 13:00:57
·
answer #3
·
answered by ♥♥♥H뮧hË¥™♥♥♥ 6
·
1⤊
1⤋
You need to solve for one variable of choice and then substitute the value of that variable into the other equation.
LOOK:
For x - 3y = - 3, I will solve for x by adding 3y to BOTH sides of the equation.
We have this:
x = 3y - 3
I will plug 3y - 3 into -2x + 7y = 10 to find y.
Here we go:
-2(3y-3) + 7y = 10
Next: Multiply every term inside the parentheses by the outside
-2. See it?
We get:
-3y + 6 + 7y = 10
Next: combine like terms on the LEFT SIDE of the equation.
We get this:
4y + 6 = 10
4y = 10 - 6
4y = 4
y = 1.
Next:
Select one of the ORIGINAL EQUATIONS given to you and plug y to find the value of x.
I decided to pick x - 3y = -3.
Here it is:
x - 3(1) = -3
x - 3 = -3
x = 0
Solution and final answer is: {x = 0, y = 1}
Guido
2006-11-12 13:04:12
·
answer #4
·
answered by Anonymous
·
3⤊
0⤋
-2x+7y=10
x-3y=-3
Solve for x in equation 1
x= 3y-3
then plug in the x into the first equation
-2(3y-3) + 7y = 10
-6y + 6 + 7y = 10
y + 6 = 10
y = 4.
Plug in y back into equation 2 and you will get what x equals.
x - 3(4) = -3
x - 12 = -3
x = 9
y = 4, x = 9
2006-11-12 12:56:41
·
answer #5
·
answered by aplpie 3
·
3⤊
1⤋
(1) -2x+7y=10
(2) x-3y=-3 (2a) x=3y-3
substitute (2a) into (1)
-2(3y-3)+7y=10
-6y+6+7y=10
y=4
from (2a)
x=3*4-3=12-3=9
x=9
y=4
2006-11-12 12:59:33
·
answer #6
·
answered by yupchagee 7
·
3⤊
1⤋
x - 3y = -3
Add 3y to each side
x = 3y - 3
Replace x with 3y-3 in the first equation
-2(3y-3) + 7y = 10
-6y + 6 + 7y = 10
y + 6 = 10
y = 4
x = 3y - 3 = 3(4) - 3 = 12 - 3 = 9
Answer: (9,4)
2006-11-12 12:55:22
·
answer #7
·
answered by MsMath 7
·
4⤊
3⤋
x = 3y - 3
Put this into the first equation and solve for y. Then go back to x = 3y - 3 to find x.
2006-11-12 12:59:37
·
answer #8
·
answered by Dr. J. 6
·
3⤊
1⤋
1. you can use elimination: multiply the second equation by 2: 2x-6y=-6, and then add the two equations and get: 4y=7
2. or you can use subtitution: x=-3+3y is subtituted in the first equation.
Good Luck.
2006-11-12 12:58:05
·
answer #9
·
answered by Serious 4
·
1⤊
1⤋